CONSPECTUS OF NURALI КАBUL’S CREATURE (Scientific journal of the Fergana State University, 2023)
The success of reforms in society largely depends on the spiritual and social level of members of the society. In the formation of any human spirituality, fiction has a wide range of possibilities. In this sense, there is a need for systematic study of Nurali Kabul’s work in Uzbek prose. This article sums up the work on the occasion of the 70th anniversary of the writer.